An Update on Biologics in Pediatric Asthma: A Canadian Perspective (Actualité en allergologie et en immunologie au Canada, 2025)
Asthma is one of the most common chronic diseases in Canada, affecting approximately 11% of Canadians. Severe asthma, estimated to affect 5–10% of patients with asthma, is associated with a significant burden of disease‑related morbidity. In adults, typical management strategies include using combinations of inhaled corticosteroids, long-acting beta agonists, leukotriene receptor antagonists, long-acting muscarinic antagonists, and oral corticosteroids. However, in pediatric cases, particularly young children, our medication options are more limited. Although inhaled corticosteroids are effective for the majority of mild-to-moderate asthma cases, their efficacy in non-atopic asthma is limited.  Furthermore, using inhaled corticosteroids at moderate-to-high doses can impair linear growth and lead to adrenal suppression. Given our growing recognition of asthma as a heterogenous disease, with multiple disease endotypes driven by distinct inflammatory pathways, there is an increasing demand for targeted therapies, particularly for patients with ongoing, uncontrolled disease (Figure 1). Type 2 (T2) high inflammation, characterized by elevated levels of IgE, interleukin (IL)-4, IL-5, and IL-13, alongside eosinophilia and atopy, remains the most well-defined endotype in school-age children and youth. With the advent of biologic medications, targeting T2‑high inflammatory pathways has become a critical component for managing uncontrolled, moderate‑to-severe asthma in children. This approach aims to improve treatment response and reduce adverse effects. This review will explore the biologic therapies currently available in Canada for moderate-to-severe pediatric asthma, discuss key considerations in selecting the optimal biologic, and outline future research directions to inform the optimal timing for initiating and discontinuing biologic treatments.